Promotion of beekeeping as a potential option for agriprenureship: Insights in context of Mann Ki Baat (Inner thoughts) - MOHANTY, A K; BORDOLOI, R M; T, AMRUTHA; SINGHA, A K; KUMAR, BAGISH; ATHARE, TUSHAR; JHANGID, B L; KESHAVA; KUMAR, ANJANI (The Indian Journal of Agricultural Sciences, 2023)
Scientific beekeeping can be a potential and possible emerging entrepreneurial option for the smallholders’ livelihood security. It stimulates economic transformation, helps in economic and nutritional security and enhances ecological resilience as emphasized by Hon’ble Prime Minister of India in his 91st episode of Mann Ki Baat, aired on 31 July 2022. The present study has examined the critical factors responsible for the success of beekeeping under various farming systems with a focus on individual/group beekeepers. Using a semi-structured interview schedule, the study was conducted with a sample size of 40 individual beekeepers and 40 group beekeepers (comprising of 2,221 members) selected purposively from 26 States/UTs covering 56 districts of the country. Middle aged beekeepers (47.50%) within the range of 35–50 years were observed to be more enthusiastic for beekeeping enterprise showing optimal gender discrimination with the male dominance of 92% and 77% in case of individual and group, respectively. Capacity built by KVKs with before and after Mann Ki Baat episodes facilitations, was perceived to be inspiring 32.50% individual and 25% group beekeepers to venture agri-business enterprise in beekeeping. In case of marketing of honey and honey-based products, middlemen intervention was more in case of individual (22%) as compared to group (6%), whereas the group (24%) had a better dominance in online marketing system than the individual (8%). Beekeeping proved to be a profitable enterprise as the group farmers earned a net income of ₹1,28,328 and the individual beekeepers with a net income of ₹92,947 per 50 bee hives with B:C ratio of 1.45 and 1.55, respectively. This has also been in tune of Hon’ble Prime Minister’s emphasis on beekeeping as an alternative source of income for sustainable livelihood highlighted at the national conclave on natural farming on 16 December 2021. The study also revealed that ‘pesticide residual problems’, ‘low level of knowledge on honey quality parameters’ and ‘lack of proper storage facility’ were some of the major obstacles faced by the individual and group beekeeping enterprises. The paper also accentuates on the challenges faced by the beekeeping sector and suggests strategies for its expansion as a viable business enterprise.